Pendekatan Wirausaha Sosial Dalam Pemanfaatan Bantuan Langsung Tunai (BLT) Dana Desa Bagi Masyarakat Miskin di Masa Pandemi Covid-19 - Subhan Purwadinata; Nadia Nuril Ferdaus; Ali Akbar Hidayat (CV. Ulil Albab Corp, 2024)
This study aims to examine in depth the social entrepreneurial approach in utilizing Village Fund Direct Cash Assistance (BLT) for the Poor during the Covid-19 Pandemic in Kukin Village, North Moyo District, Sumbawa Regency. This research is descriptive qualitative. The methods used to collect data are interviews and literature study. Informants in this study were the Village Head, Village Secretary, Treasurer, Chair of the Village Consultative Body (BPD), Village Professional Facilitator, one of the beneficiary communities during the Covid-19 pandemic which was used for entrepreneurial activities by recipients of village funds. The data used in this study is qualitative data which is used as field data that tries to observe, know and describe factual conditions in the field. Data were analyzed using Miles and Huberman's interactive analysis. The results of the study showed that the use of village funds during the COVID-19 pandemic had been carried out in accordance with the rules, namely prioritizing the use of village funds, especially BLT-Village Funds used for Covid-19 countermeasures and the welfare of the community receiving BLT Village funds assistance, namely the poor through efforts to increase morale social entrepreneurs in the recipient community so that they can become new entrepreneurs so that the assistance received can increase the income of the poor recipients of assistance. The use of village funds in the Villages of North Moyo Regency itself is more focused on COVID-19 response villages and direct cash assistance from village funds (BLT-DD in the era of the COVID-19 pandemic).